2016
DOI: 10.1111/ane.12604
|View full text |Cite
|
Sign up to set email alerts
|

Language improvement one week after thrombolysis in acute stroke

Abstract: Lesion size and initial aphasia severity are the main predictors of aphasia recovery one week after thrombolysis. A NIHSS composite verbal score seems to capture the global linguistic performance better than the language item alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…With respect to demographic predictors, previous studies that have assessed general aphasia recovery have found that variables such as younger age, being female, higher educational attainment, and lower initial stroke severity are associated with better recovery (5,(32)(33)(34)(35)(36)(37). However, the role of these demographic factors in the recovery and outcome of auditory comprehension deficits in aphasia more specifically has not been well-studied and findings have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to demographic predictors, previous studies that have assessed general aphasia recovery have found that variables such as younger age, being female, higher educational attainment, and lower initial stroke severity are associated with better recovery (5,(32)(33)(34)(35)(36)(37). However, the role of these demographic factors in the recovery and outcome of auditory comprehension deficits in aphasia more specifically has not been well-studied and findings have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Items 1b (LOC questions) add questions about the month and age, and item 1c (LOC commands) add onestage commands. As noted in Table I, additional language assessments used included the Language Screening Test (LAST) (Denier et al, 2016); the Western Aphasia Battery (WAB) (Finch et al, 2014); the French version of the Boston Diagnostic Aphasia Examination (BDAE) (Jacquin et al, 2014); the Lisbon Aphasia Assessment Battery (BAAL) (Martins et al, 2016); and the Basel-Minnesota test (Engelter et al, 2006). The study by de Oliveira and Damasceno (2011) diagnosed aphasia with a collection of informal language tasks described as spontaneous narrative, fluency, yes/no and three stage command, naming six objects and ideomotor praxis.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The data extracted from this analysis is presented as a harvest plot in Figure 2. None of the studies received the maximum score of 14, the highest score (11), was received by only four studies (Kohrmann et al, 2009;Kremer et al, 2013;Lundstrom et al, 2015;Martins et al, 2016). A strength of all studies were the conclusions, the conclusions were deemed appropriate in all but two studies, Mazza et al (2012) and Saarinen et al (2015).…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations